An assessment of financial and supply chain management outcomes in Western Cape public hospitals - Lewis, Hendrik Archie (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2005.